2000
DOI: 10.1007/s001340051284
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delayed repair and elective high-frequency oscillatory ventilation on survival of antenatally diagnosed congenital diaphragmatic hernia: first application of these strategies in the more “severe” subgroup of antenatally diagnosed newborns

Abstract: The prognosis of antenatally diagnosed CDH was improved by systematic HFOV on admission, no systematic transfer, and delayed surgery. This improvement is associated with modification of postnatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 29 publications
3
47
1
6
Order By: Relevance
“…These were very sick patients with overwhelming pulmonary hypoplasia and associated hypertension. The role of HFOV in CDH remains uncertain because of conflicting results [4,20,21]. Inhaled NO was given to only two patients and the benefit in the management of CDH in this series is uncertain.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These were very sick patients with overwhelming pulmonary hypoplasia and associated hypertension. The role of HFOV in CDH remains uncertain because of conflicting results [4,20,21]. Inhaled NO was given to only two patients and the benefit in the management of CDH in this series is uncertain.…”
Section: Discussionmentioning
confidence: 83%
“…With the management of CDH including delayed surgery, extracorporeal membrane oxygenation (ECMO), high-frequency oscillatory ventilation (HFOV), inhaled nitric oxide (NO), exogenous surfactant, partial liquid ventilation and synchronized ventilation, the survival rate ranges from 53 to 90% [1][2][3][4][5][6][7][8]. After Sakai et al [9] reported that early surgical repair may reduce pulmonary compliance, impede mechanical ventilation and increase circulatory instability, the treatment of CDH is no longer considered a surgical emergency.…”
Section: Introductionmentioning
confidence: 98%
“…CDH consists of a combination of pulmonary hypoplasia, abnormal pulmonary vascular growth, and a defect of the diaphragm that allows abdominal viscera to move up into the chest cavity. Despite the many advances in medical therapy and although better survival rates have been published [34,35], the mortality rate in CDH still remains around 20-40%. In the survivors, a variety of symptoms has been reported especially in the first years of life [36][37][38], but eventually most CDH survivors enjoy healthy lives [39][40][41].…”
Section: Settingmentioning
confidence: 99%
“…4 La historia quirúrgica de estos pacientes se ha modificado a través de los años, desde la intervención y reparación de manera inmediata hasta la intervención tardía de semanas o meses después de resolverse la hipertensión pulmonar del paciente. [5][6][7] Kays, et al, sugiere enfocarse de manera inmediata en los pacientes con factores de alto riesgo para entrar en ECMO y con el hígado herniado (considerado también con un factor de pobre pronóstico) y en los pacientes con un riesgo moderado de requerir ECMO, para una reparación de forma tardía y generar una sobrevida mayor al 80%, en ambas situaciones de presentación. 8 Históricamente, la terapia con membrana de oxigenación extracorpórea (ECMO), desde su primer caso, se reportó exitoso en el año de 1975 por el Dr. Robert Barlett; 9 éste se ha convertido en el estándar de manejo en pacientes críticamente enfermos en diferentes países, específicamente en los que no pueden ser oxigenados de ninguna forma, a pesar del manejo especializado con medicamentos y ventilación mecánica asistida; siguiendo los protocolos de manejo de la Organización de Soporte de Vida Extracorpórea (ELSO) y en base a la siguiente fórmula de índice de oxigenación:…”
Section: Introductionunclassified